EFFECT OF MAGNETITE AND CHITOSAN-MAGNETITE ADDITION ON BACTERIAL LEVELS AND NH3-N (FREE-LIVING N2-FIXING BACTERIA CULTURE) - Umar, Ali; Saprudin, Deden; Hazra, Fahrizal (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
Free-living N2-fixing bacteria are essential in the soil because they provide a source of nitrogen in the form of ammonium needed by plants to be used in building protein blocks. The fixation of free N2 needs to be increased by adding nanomaterials such as magnetite (Fe3O4), which has an active group and can be a source of nitrogenase enzyme cofactor. In this study, increased N2 fixation used N2-fixing bacteria in Burks medium. This increase was determined by measuring NH3 levels using the Phenate method formed after Burks medium was treated with Fe3O4 and chitosan-magnetite (CS-Fe3O4). The study found that the number of bacteria can be well decreased. This research showed that using Fe3O4 and CS-Fe3O4 increased NH3-N levels in cultures of free-living nitrogen-fixing bacteria by 15.40% and 75.54%. For future development, it can be in the form of optimization, the effect of adding the same material to plant secondary metabolites, and the mechanism of bacteria in using the material.